THE INFLUENCE OF DIGITAL MARKETING AND BRAND IMAGE ON PURCHASE DECISIONS: A STUDY ON THE ONLINE-BASED CULINARY INDUSTRY - Kadar Nurjaman; Babay Suhaemi; Heri Sutanto; Rahmawati; Lilis Sulastri (UIN Sunan Gunung Djati Bandung, 2025)
The rapid development of digital technology has significantly transformed the marketing landscape, particularly in the culinary industry, where online platforms have become a primary medium for attracting and retaining customers. This study aims to analyze the influence of digital marketing and brand image on purchase decisions in the online-based culinary industry. The research employed a quantitative approach with 200 respondents who had purchased food or beverages through online platforms such as GoFood, GrabFood, and ShopeeFood in Indonesia. Data were analyzed using multiple regression analysis. The results indicate that both digital marketing and brand image have a significant positive influence on purchase decisions. Among the two variables, brand image showed a stronger effect, suggesting that customers’ perceptions and emotional connections with a brand play a crucial role in shaping their purchasing behavior. These findings contribute to the understanding of how online culinary businesses can optimize marketing strategies to enhance brand value and customer loyalty.